Towards an understanding of empathy for the good and bad fortunes of others - Bodley Scott, Sarah E.M. (2011)
Empathy and consideration for other people's feelings are at the very heart of our ability to form and maintain social relationships, but this may sometimes demand looking beyond our own emotional perspective. This thesis sought to investigate cognitively-evoked empathy (in the absence of direct cues to other people's emotions), and its modulation. A new behavioural paradigm was first developed to study emotional perspective-taking in situations in which individuals have contrasting emotional experiences. In this paradigm participants were presented with written scenarios featuring them self and/or another person and were asked to imagine how they or the other person would feel in each scenario, making speeded emotion judgments. The scenarios described a wide variety of everyday events that might be expected to elicit positive or negative feelings in the protagonist (s) and involved conflict (contrasting fortune) or no conflict between the perspectives of self and other. Using this paradigm, it was found that individuals were sensitive to another person's conflicting perspective when judging how they would feel in emotional situations, and were particularly sensitive to another person's negative perspective. This was born out in eight further experiments, which revealed a negative-positive asymmetry in empathy, showing empathy for bad fortune to be greater and less dependent on the empathiser's own emotional experience than empathy for good fortune. Low-level accounts of how information about another person's fortune might modulate emotional judgments were discussed in relation to two experiments, but were considered insufficient to explain the data. Evidence for the involvement of higher-level processes was then found in the following five experiments. In the first three of these, participants were found to anticipate empathy in others, but to a lesser extent than in self. Then, in the final two experiments, effects of person appraisals (i.e. the likeability of the other) on empathy for the good and bad fortunes of another were observed, but it was also found that these effects were moderated by individual differences in dispositional empathy and moral attitudes. All these findings are discussed in relation to current theoretical ideas of empathy and mental state understanding.